Watching self from a distance: The whys of watching sinetrons among Malay-Javanese women in Malaysia - Rofil, Lily El ferawati (Informasi, 2017)
This article discusses the cognitive reasoning behind the love for watching sinetron expressed by Malay-Javanese women in Malaysia. The Malay-Javanese women in this context refer to female members of Javanese communities within Malay society. Malaysians of Javanese descent are constitutionally considered as ethnic component of Malay racial group due to similarities in cultural customs and religion of Islam. However, they retain some semblance of Javanese cultural heritage including speaking the language in their everyday life. In the context of Malay-Javanese women under this study, it is identified that sinetrons have become the main source of their cultural consumption from television. Sinetrons are soap opera-like television productions from Indonesia"”the country where their ancestors were originated from. The results from ethnographic fieldwork in Kampung Papitusulem of Selangor show how these women incline to watching sinetrons to a certain level, primarily due to three main reasons. First, the dialogues in the television productions fit their language preference. Second, they can find representations of their cultural identity in the images of sinetrons. Third, they watch the imported television program from Indonesia simply for the identification of sense of belonging. It is argued that viewing sinetrons for these women represents watching self from a distance, which is central discussion in cultural and media studies.Artikel ini membicarakan pemikiran kognitif di sebalik kecintaan menonton sinetrondalam kalangan wanita Melayu-Jawa di Malaysia. Wanita Melayu-Jawa dalam konteksini merujuk pada warga perempuan dari komunitas Jawa dalam masyarakat Melayu.Menurut Konstitusi Malaysia, warga negara Malaysia keturunan Jawa dianggapsebagai komponen etnik dari kelompok bangsa Melayu karena memiliki kesamaan adatbudaya dan keyakinan sebagai Muslim. Pada hakikatnya, mereka masih mengekalkanbeberapa komponen warisan budaya Jawa seperti penggunaan Bahasa Jawa dalamkeseharian mereka. Dalam konteks wanita Melayu-Jawa yang dibahas dalam artikel ini,diketahui bahwa sinetron telah menjadi salah satu sumber budaya termediakan olehtelevisi yang mengeratkan pertalian dengan asal usul mereka. Sinetron merupakanproduksi televisi yang tergolong genre opera sabun berasal dari Indonesia"”negarayang menjadi tanah kelahiran pendahulu wanita tersebut. Hasil dari kerja lapanganetnografi, di Kampung Papitusulem, Selongor, menunjukan bagaimana wanita-wanitaini menyukai sinetron pada tahap tertentu karena tiga alasan utama. Pertama, dialogyang digunakan dalam sinetron sesuai dengan preferensi mereka. Kedua, mereka dapatmenemukan identifikasi identitas budaya mereka dalam representasi sinetron. Ketiga,mereka menonton program televisi yang diimport dari Indonesia sebagi ekspresi rasamemiliki terhadap Indonesia. Ini menunjukkan bahwa menonton sinetron bagi wanitaMelayu-Jawa mempunyai makna seperti melihat identitas diri dari kejauhan, dan inimerupakan diskusi sentral dalam kajian media dan budaya.